2020
DOI: 10.3390/rs12071108
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of an Automated Calibration of the SEBAL Algorithm to Estimate Dry-Season Surface-Energy Partitioning in a Forest–Savanna Transition in Brazil

Abstract: Evapotranspiration ( E T ) provides a strong connection between surface energy and hydrological cycles. Advancements in remote sensing techniques have increased our understanding of energy and terrestrial water balances as well as the interaction between surface and atmosphere over large areas. In this study, we computed surface energy fluxes using the Surface Energy Balance Algorithm for Land (SEBAL) algorithm and a simplified adaptation of the CIMEC (Calibration using Inverse Modeling at Extreme Condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 108 publications
(169 reference statements)
0
20
0
1
Order By: Relevance
“…In fact, the high accuracy of the in situ flux data used contributed to the good performance of the daily estimates. However, it is important to highlight that this is not a restriction, because hourly radiation data are available for the whole globe and can be easily obtained from several reanalysis products and used to generate trustable and continuous daily ET series [56].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the high accuracy of the in situ flux data used contributed to the good performance of the daily estimates. However, it is important to highlight that this is not a restriction, because hourly radiation data are available for the whole globe and can be easily obtained from several reanalysis products and used to generate trustable and continuous daily ET series [56].…”
Section: Discussionmentioning
confidence: 99%
“…While flux tower measurements have shown, at local scales, that land cover changes can impact water and energy fluxes (von Randow et al., 2004), large scale assessment with satellites based on both energy balance and physical‐based equations driven by vegetation phenology and meteorological reanalysis have reinforced these findings (Baker & Spracklen, 2019; Khand et al., 2017; Laipelt et al., 2020; de Oliveira et al., 2019). All these studies demonstrated significantly lower ET rates under pasture, agricultural, and deforested areas than in primary and secondary forests (von Randow et al., 2020).…”
Section: Evapotranspirationmentioning
confidence: 99%
“…Our understanding about energy partitioning in the Amazon biome has improved through RS models (de Oliveira et al., 2019; Laipelt et al., 2020). For example, high resolution ET estimates using SEBAL in the south‐western Amazon demonstrated significant differences among energy and water fluxes in forests and non‐forest areas, such as pasture and cropland.…”
Section: Evapotranspirationmentioning
confidence: 99%
“…Among the most used models, the surface energy balance algorithm for land (SEBAL) has been successfully applied in different climatic regions and land covers [6]. SEBAL integrates orbital and meteorological data to compute SEBFs and ET [7].…”
Section: Introductionmentioning
confidence: 99%